Treatment of pemphigus vulgaris: part 1 – current therapies. (3rd October 2019) - Yanovsky, Rebecca L.; McLeod, Michael; Ahmed, A. Razzaque
ABSTRACT: Introduction : While biologic agents that can be used for treating pemphigus vulgaris (PV) are increasing, themajority of the world's PV patients can afford only corticosteroids (CS) and some immunosuppressive agents (ISA). Areas covered : The spectrum of side effects encountered when PV patients receive high-dose, long-term CS and ISA are presented based on total dose and duration of therapy. The steroid-sparing effect of individual ISA as documented in published studies and their clinical outcomes, in terms of duration of remissions, frequency of relapses and time to relapse, are presented, so that comparisons are possible. Thus, rational choices can be made for the individual patient. Expert opinion : In 2019, the majority of PV patients globally will continue to be treated with CS and ISA. This review will help clinicians and patients become aware of when to anticipate which side effects and if possible, to prevent or avoid them. It provides guidelines to maximize the clinical benefits of ISA in inducing and maintaining remission and minimizing side effects by monitoring them.